Psycho-social Development of Thalassemic and Healthy Adolescents: Comparative Study - Saeed, Wasan Bashir; Aldoori, Nuhad Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
Thalassemia is the most common genetic disease in the world, characterized by a reduction or absence of normal hemoglobin synthesis. It has an impacts on the progress of growth and development, which leads to increase the worries about physical appearance, interfere with the process of gaining independence and healthy relationships with parents and friends. To identify the psychosocial development of thalassemic patient and healthy adolescents, As well as to a comparison between the studied variables of thalassemic and healthy adolescents. A cross- section descriptive study design was used through a period from 1st of September 2019 to 15th of May 2020; in the Babylon province on a sample consisted of (100) thalassemic patients at Babylon for maternity and pediatric teaching hospital; selected 20% of the adolescent thalassemic patients and (100) from healthy adolescents in secondary school; nominated by simple random stratified method. The data collected by using an adopted questionnaire and analyzed electronically by using SPSS program Version 26. The majority of thalassemic patients aged between (13-14) years old as male gender, while the majority of healthy adolescents were females aged between (15-16) years. There was a significant difference between healthy and thalassemic adolescents in relation to overall psychosocial development at (0.001). After all, there a significant difference between thalassemic and healthy adolescents in psychosocial development, and recommended to further researches are requires to investigate growth and development in different age group on a wider sample may include all centers in the country.